2020
DOI: 10.1111/jfd.13244
|View full text |Cite
|
Sign up to set email alerts
|

Mourilyan virus pathogenicity in kuruma shrimp (Penaeus japonicus)

Abstract: The bunyavirus Mourilyan virus (MoV) occurs commonly in Black tiger (Penaeus monodon) and kuruma shrimp (Penaeus japonicus) farmed in eastern Australia. There is circumstantial evidence of MoV causing mortalities among P. japonicus moved from farm ponds to tanks for rearing as broodstock. To directly assess its pathogenic potential, independent cohorts of pond‐ (n = 24) or tank‐reared juvenile (n = 21) P. japonicus were challenged intramuscularly with a cephalothorax tissue homogenate of P. monodon containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“… Rajendran et al (2006) reported the detection of up to > 10 4 copies/ng-RNA (> 10 7 copies/μg-RNA in the paper) of MoV in lymphoid organs of challenged P. japonicus associated with an increase of lymphoid spheroids. It has been experimentally confirmed that MoV infection can cause gradually accumulating mortality in P. japonicus ( Cowley, 2020 ). However, Oanh et al (2011) confirmed that P. monodon can tolerate a high-level MoV infection up to > 10 6 copies/ng-RNA (>10 9 copies/μg-RNA in the paper) in gills and that mortalities of the mid-crop mortality syndrome (MCMS) outbreaks are associated with the co-infection with gill-associated virus (GAV) rather than MoV.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… Rajendran et al (2006) reported the detection of up to > 10 4 copies/ng-RNA (> 10 7 copies/μg-RNA in the paper) of MoV in lymphoid organs of challenged P. japonicus associated with an increase of lymphoid spheroids. It has been experimentally confirmed that MoV infection can cause gradually accumulating mortality in P. japonicus ( Cowley, 2020 ). However, Oanh et al (2011) confirmed that P. monodon can tolerate a high-level MoV infection up to > 10 6 copies/ng-RNA (>10 9 copies/μg-RNA in the paper) in gills and that mortalities of the mid-crop mortality syndrome (MCMS) outbreaks are associated with the co-infection with gill-associated virus (GAV) rather than MoV.…”
Section: Discussionmentioning
confidence: 97%
“…In P. japonicus, elevated MoV infection loads were associated with gradually increased mortality in shrimps reared in tanks following their grow-out in farm ponds (Sellars et al, 2006). Its pathogenic potential has been confirmed recently in experimental challenge trials (Cowley, 2020).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation